Extremely low surface recombination in 1 Ω cm n-type monocrystalline silicon - Bonilla Osorio, R; Reichel, C; Hermle, M; Wilshaw, P (Wiley, 2016)
A key requirement in the recent development of highly efficient silicon solar cells is the outstanding passivation of their surfaces. In this work, plasma enhanced chemical vapour deposition of a triple layer dielectric consisting of amorphous silicon, silicon oxide and silicon nitride, charged extrinsically using corona, has been used to demonstrate extremely low surface recombination. Assuming Richter’s parametrisation for bulk lifetime, an effective surface recombination velocity Seff = 0.1 cm/s at Δn = 1015 cm–3 has been obtained for planar, float zone, n-type, 1 Ω cm silicon. This equates to a saturation current density J0s = 0.3 fA/cm2, and a 1-sun implied open circuit voltage of 738 mV. These surface recombination parameters are among the lowest reported for 1 Ω cm c-Si. A combination of impedance spectroscopy and corona-lifetime measurements shows that the outstanding chemical passivation is due to the small hole capture cross section for states at the interface between the Si and a-Si layer which are hydrogenated during nitride deposition